Australian Cockroach Periplaneta australasiae Fabricius (Insecta: Blattodea: Blattidae) - Shiyao Jiang; Phillip E. Kaufman (EDIS)
Australian cockroaches are the most common outdoor cockroach in southern Florida. Though they typically stay outdoors, Australian cockroaches may also venture inside and live among humans. This 4-page fact sheet covers the Australian cockroach’s distribution and habitat, biology, medical risks to humans, and management as a pest. Written by Shiyao Jiang and Phillip E. Kaufman, and published by the UF Department of Entomology and Nematology, April 2015.